2018
DOI: 10.1177/1369433218766946
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of temperature actions on flat steel box girders of long-span bridges with temperature monitoring data

Abstract: The worldwide application of streamlined flat steel box girder on long-span bridges calls for more knowledge of its temperature distribution. The rapid development of structural health monitoring techniques offers a great opportunity to address this issue. A comprehensive approach of installing monitoring equipment, collecting data, and applying long-term temperature monitoring data to study the temperature distribution of flat steel box girders is developed. As demonstrated through the analysis of 1-year data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…According to previous experiments and measurement data research, [4][5][6][7][8] it can be found that the mechanism of the vertical positive temperature gradient model is the 1-dimensional heat conduction from the top to the bottom of the concrete slab caused by solar radiation. Thereby, the produced temperature distribution along the height of the section is not uniform, while temperature differences of the longitudinal and horizontal usually can be ignored.…”
Section: Temperature Load Devicementioning
confidence: 99%
See 1 more Smart Citation
“…According to previous experiments and measurement data research, [4][5][6][7][8] it can be found that the mechanism of the vertical positive temperature gradient model is the 1-dimensional heat conduction from the top to the bottom of the concrete slab caused by solar radiation. Thereby, the produced temperature distribution along the height of the section is not uniform, while temperature differences of the longitudinal and horizontal usually can be ignored.…”
Section: Temperature Load Devicementioning
confidence: 99%
“…3 To understand the temperature change law of the bridge structures under the influence of solar radiation and the environment, researchers were conducted many long-term testing studies on long-span bridges which in service through solar radiation tests or based on the established Structural Health Monitoring (SHM) system. [4][5][6][7][8] Hossain et al 9 showed that the additional positive restraint moment caused by the initial thermal stress and thermal gradient could exceed the tensile strength of concrete and cause cracking. Song et al 10 researched the influence of solar temperature gradient on the construction of concrete continuous box girder bridges by FE method and found that the maximum longitudinal and horizontal tensile stresses of the girders are 2.67 and 4.41 MPa, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The block maximum method is a typical EVA method in practical applications [48]. The block maximum model is built up by 3 steps: (1) dividing all observations into k groups on average; (2) extracting the maximum value in each group for discussion; and (3) performing distribution analysis using the extracted maximum data.…”
Section: Determination Of Thresholdmentioning
confidence: 99%
“…Traditionally, there are two main methods to analyze the temperature gradient model. The first method employs finite element method (FEM) to calculate the temperature field of the whole structure based on the theory of heat transfer (Deng et al, 2018; Tong et al, 2001; Zhou et al, 2016). While this method can provide the temperature model for the entire structure at any time, it requires huge computational cost to get the temperature gradient model for the girder’s service life.…”
Section: Introductionmentioning
confidence: 99%